Qualidade de vida de pacientes submetidos à radioterapia para tratamento de lesões malignas de cabeça e pescoço - Souza, Fátima Regina Nunes de [UNESP] (2013)
In order to evaluate the quality of life of patients with head and neck cancer, this study analyzed data of 24 patients with squamous cell carcinoma, which indicated therapy was radiotherapy or not be combined with chemotherapy and surgery. The study was conducted in the Unit of Radiotherapy of Megavoltage located in the São José de Rio Preto-SP, in the period August 2007 to January 2008. Then, it was used the questionnaire of quality of life from University of Washington which enabled the identification of different quality of life patterns associated with the different stages of radiotherapy, indicating to be viable the prospect of recognition of prognostic factors of reduction in multiple domains of quality of life. From the data collected and analyzed, it was identified that the areas with the worst score in the begin of radiotherapy were appearance, speech and anxiety; during the treatment were taste, saliva and anxiety; and in the end were taste, saliva and swallowing. Throughout the treatment, it was observed the deterioration of patients' mood. In this regard, emphasizes the importance of dental and psychological follow-up, within the framework of a multidisciplinary care for patients with head and neck cancer during radiotherapy treatment.